High Heels, Empty Bottles and Other Interesting Pedagogical Artefacts Mediating Social Movement Learning - Saccucci, Brent Franco; de Oliveira Jayme, Bruno (Journal of the Canadian Association for Curriculum Studies, 2020)
How does individual transformation unfold within social movement learning, a territory that mainly embodies learning as a collective practice? How do the visual and performing arts, as research tools, mediate such individual transformation while simultaneously promoting community engagement and critical dialogue amongst members of social movements and the general public? Interweaving social movement and transformative learning theories along with queer performance theory, this arts–based and participatory study answers these questions by describing and articulating two art interventions and the subsequent discourse and politics that emerged from these two scenarios. The first scenario unfolded during a series of painting workshops facilitated with members of the National Recycling Social Movement (MNCR) in 2017 in São Paulo, Brazil. The second scenario unfolded as a series of drag performances in Edmonton, Canada. By exploring the potentialities of visual and performing arts to understand social movement learning through the arts, people were asked to engage internal and external dialectical relationships that mediate their construction of visual and performative thought. Such creative thinking awakened a higher level of human consciousness, enabling individuals to construct new knowledge. This new knowledge empowered participants and enabled an agency which they later used to promote community development and social change.